Self-monitoring improved child feeding among low educated slum mothers in Bangladesh, a pilot study. (30th September 2020) - Jannat, K; Rahman, M; Agho, K; Parvez, S; Merom, D
Abstract: Issue: Child undernutrition in urban slums is the most serious but least addressed health problem in many LMICs including Bangladesh. Slum children are deprived of adequate feeding as advocated by WHO. Face-to-face contact to monitor adherence to child feeding recommendations is costly. We aimed to identify if a visual aid for self-monitoring, in the form of a pictorial calendar, could assist illiterate slum mothers to self-regulate their child feeding behaviours and increase adherence to recommended child feeding practices. Description of the practice: A mixed method study was conducted (Randomised Controlled Trial + semi-structured qualitative interviews) over four weeks in a slum area of Dhaka city. Thirty-four mothers to child aged 6-23 months having <5 years of education were recruited. Mothers randomized to intervention arm (n = 17) received an hour of complementary feeding education along with a pictorial calendar and color-coded stickers representing food groups. The control arm received the education session only. The primary outcome was Minimum Dietary Diversity (MDD: ≥4 food groups in past 24 hours); the Generalised Estimation Equations (GEE) with a log link and binomial family was used to test treatment by time interactions. Results: The proportion of achieving MDD was more common (RR 1.2, 95%CI 0.8, 1.8) among mothers from intervention arm compared to control mothers. Intervention mothers were more likely to identify the appropriate food groups compared to control mothers. More than 80% of the mothers completed the calendar for all 28 days of study duration. During qualitative interviews, most mothers (4/5) stated that the pictorial calendar acted as a reminder for them. Lessons: An encouraging tendency towards better complementary feeding and better knowledge was seen among the intervention mothers compared to controls. Future research with a larger sample is needed to establish the significance of effect size. Key messages: Pictorial calendar appeared to help sustain knowledge and improve feeding practices. Self-monitoring using a pictorial calendar could be a good visual aid for low-educated mothers from low socio-economic status.